Impacts of home-care subsidies: Evidence from quasi-random assignment - Ofek-Shanny, Yuval; Strulov-Shlain, Avner; Zeltzer, Dan (Journal of Public Economics, 2025)
We study the impact of subsidizing home-based long-term care on recipients’ health and the labor supply of their working-age children. We use administrative data from Israel on the universe of welfare benefit applications linked with tax records of applicants and their adult children. To address the endogeneity of benefit recipients’ health status, we instrument for benefit receipt using the leniency of randomly assigned evaluators who assess the applicant's functional status and determine benefit eligibility. We find that for compliers—applicants who receive subsidies only from more lenient evaluators—subsidizing home-based care has large adverse effects on recipient health (+5.2 p.p. one-year mortality, 95 % CI: 1.5 to 8.9 p.p.) but no detectable effects on their children's labor market outcomes (child labor market participation: −0.5 p.p., 95 % CI: −5.2 to +4.2 p.p.; child income: −5.5 log points, 95 % CI: −46 to +35 log points). The results are consistent with the crowd-out of self-care for the marginal recipient, highlighting the need to assess the heterogeneous effects of home-care subsidies.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Home-based long-term care; Labor supply